PENGARUH INTERAKSI TEMAN SEBAYA DI LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER BERSAHABAT SISWA KELAS VI MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Nur Istiqomah, Laili; Iswandi, Irvan; Humaeroh, Iis (Cahaya Ilmu Bangsa Institute, 2024)
The purpose of this study was to determine the effect of peer interaction in the school environment on the formation of friendly character of 6th grade students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. This research uses quantitative methods with descriptive analysis type of research. Data collection was carried out by distributing questionnaires to 6th grade students of MI Ma'had Al-Zaytun in the 2024/2025 academic year which is the population of this study. Determination of the sample in this study was carried out using purposive sampling technique which obtained a sample size of 67 students from a total population of 204 students. The results of this study indicate that interaction with peers in the school environment has a positive and significant effect on the formation of students' friendly character. This is evidenced by the tcount value which is greater than the ttable, namely 5.476 > 1.997 with a coefficient of determination of 0.316, which means that 31.6% of peer interaction variables affect the formation of friendly character. Keywords: peer interaction, school environment, friendly character building, madrasah ibtidaiyah